Modeling and clinical data exchange in registration of infectious disease cases (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2023)
The registration of communicable disease cases aims to limit their prevalence. The Ordinance on the Procedure for Registration, Notification and Reporting on Communicable Diseases, issued by the Ministry of Health, determines the rules for the implementation of the registration procedure in Bulgaria. Currently, this information is communicated by phone, email or on paper, and then the data is manually re-entered. This significantly complicates the exchange of information between health care participants. In addition, valuable information to produce reports noting disease prevalence levels is lost or fragmented. This paper aims to resolve these problems by the means of information technologies and ensure efficient storage, processing and management of data registration for patients with communicable diseases. The business process for the implementation has been studied in detail. The main roles, resources and sequence of activities at each stage of the application of the regulation have been determined. A relational database model is created for centralized storage, processing and management of data for registered patients and their contacts. An algorithm is developed and implemented for the automated determination of cases based on the symptoms of each disease specified in the regulation. ICD-10 is used, thus, creating the possibility of exchanging the collected data with international centers for tracking the spread of the disease. A three-tier application is created where web services perform the activities of registration, communication and reporting of communicable cases. The obtained results were tested with real data, consulted with experts from the health inspections and demonstrate the advantages of the developed software for fulfilling the requirements of the provisions in national legislation.